A Molecular Basis for Innovation in Drug Excipients. Issue 3 (28th September 2016) - Irwin, JJ; Pottel, J; Zou, L; Wen, H; Zuk, S; Zhang, X; Sterling, T; Shoichet, BK; Lionberger, R; Giacomini, KM
Abstract : Excipients are ubiquitous in drug formulation, ensuring that active ingredient drugs are properly released on dosing, retain their properties over time, and are palatable, among other roles. Despite their crucial roles, surprisingly little is known about their systemic availability and activities on molecular targets. Here we review key excipient properties, introduce a public‐accessible database that enumerates and categorizes them, and sketch a strategy for exploring their possible direct actions on molecular targets.